2014
DOI: 10.1213/ane.0000000000000316
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical Space Conditions During Low-Pressure Laparoscopic Cholecystectomy with Deep Versus Moderate Neuromuscular Blockade

Abstract: Deep neuromuscular blockade was associated with surgical space conditions that were marginally better than with moderate muscle relaxation during low-pressure laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(58 citation statements)
references
References 26 publications
1
53
0
3
Order By: Relevance
“…While several investigators have attempted to address this issue, almost all of these studies have (in our view) serious flaws in their study design (see above, paragraph on definitions). 6,8 The paper by Martini et al 19 was the only study that Madsen et al cite that reasonably supports the hypothesis that deep vs. moderate block may achieve superior conditions for the surgeon. The mean difference (AESD) in the subjective rating scores between the deep block post-tetanic counts (PTC) of 1-2 and moderate block groups were however very modest, only 0.7 units (4.7 AE 0.4 vs. 4.0 AE 0.4), respec-tively.…”
Section: Definitions a Fundamental Disagreementmentioning
confidence: 84%
See 1 more Smart Citation
“…While several investigators have attempted to address this issue, almost all of these studies have (in our view) serious flaws in their study design (see above, paragraph on definitions). 6,8 The paper by Martini et al 19 was the only study that Madsen et al cite that reasonably supports the hypothesis that deep vs. moderate block may achieve superior conditions for the surgeon. The mean difference (AESD) in the subjective rating scores between the deep block post-tetanic counts (PTC) of 1-2 and moderate block groups were however very modest, only 0.7 units (4.7 AE 0.4 vs. 4.0 AE 0.4), respec-tively.…”
Section: Definitions a Fundamental Disagreementmentioning
confidence: 84%
“…We do not accept the latter half of this definition and we believe that this disagreement plays a large part in why we do not concur with many of the 'Pro-' position paper conclusions. For example, the authors cite a study by Staehr-Rye et al 6 in which the authors conclude 'Deep neuromuscular blockade was associated with surgical space conditions that were marginally better than with moderate muscle relaxation during low-pressure laparoscopic cholecystectomy.' However, at a point half way through the surgical procedure, twitch height (T1) in the 'moderate NMB' group was 47% of control (a TOF count of 4 with fade), and at the 75% time point T1 was 89% of control (a TOF ratio > 0.40).…”
Section: Definitions a Fundamental Disagreementmentioning
confidence: 99%
“…condTorensma [4]2016Bariatric surgeryDeep versus moderate NMB5 point a 1 (extremely poor)–5 (optimal)310 minMean SRS, % subopt./opt. condBaete [5]2017Bariatric surgeryDeep versus moderate NMB5 point a 1 (extremely poor)–5 (optimal)1End of surgeryMean SRSCaldwell [24]1985GynaecologyNMB3 point1 (good)–3 (inadequate)UnknownUnknownSRS distributionWilliams [16]2003GynaecologyModerate versus no NMB4 point1 (poor)–4 (excellent)UnknownUnknownSRS distributionDubois [2]2014GynaecologyDeep versus moderate NMB4 point1 (optimal)–4 (unacceptable)110 minMean SRS, SRS distributionMadsen [15]2015GynaecologyDeep versus no NMB4 point1 (optimal)–4 (bad)2Fascia closureMean SRS, intra-abdominal space (cm)Taylor [19]1992General surgeryNitrous oxide5 point1 (extremely poor)–5 (very good)115 minSRS, bowel distentionStaer Rye [20]2014General surgeryDeep versus moderate NMB…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is in line with the ongoing controversial debate on neuromuscular blockade to improve surgical conditions. Whereas many publications present significantly better operating conditions during deep NMB, compared to a light block [3,4,8,14,[17][18][19], several other authors found no differences [1,15,20]. Park et al describe inconsistent results and state that "further studies are required to address the heterogeneity and power shortage demonstrated by the trial sequential analysis", in a previously published review [21].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of the NMB was defined as follows [13][14][15]: intense NMB-PTC = 0; deep NMB-TOF = 0 and PTC = 1-5; medium NMB-PTC > 5 and TOF = 0-1; shallow-TOF > 1; full recovery-TOFR > 90%. If an intense NMB was not reached with the initial dose of rocuronium, the anesthesiologist administered additional doses until a PTC = 0 could be recorded at least once for each patient.…”
Section: Anesthesiamentioning
confidence: 99%